PRINCE2 Methodology: An Innovative Way of Project Management - Saad, Saima; Abdullah, Ibrahim; Asma, Omme; Muhammad Saad, Khan; Abdul Qadir, Aneesa (2013)
The role of project management is identically indispensable for organizations nowadays and hence converted into a most important issue for implementing in modern projects. Operations and Management division is the spine of every corporate organization, and it is the key factor for progress the performance in every organization. This also includes the detailed history of project management along with the innovative modern method PRINCE2. The innovative approach of Project Management PRINCE2 (PMP2)has the generic framework,design to suit every type of project in industry. Therefore, the aim of this review to investigate the application of PRINCE2 methodology across the world due to structured method for effective project management. PRINCE2 has strongly established in UK and spread all over the world fluently; as a basic, process based approach of project management. In view of the fact that its emphasis on, the dividing the project into manageable and controllable stages. This research will encourage the implementation of Prince2 methodology it will encourage the prospect applications of PRINCE2.